LUNG TRANSPLANTATION IN CYSTIC FIBROSIS PATIENT WITH CHRONIC AIRWAYS INFECTION OF BURKHOLDERIA CEPACIA (the first case in Russian Federation) - S. V. Gautier; S. V. Golovinsky; V. N. Poptsov; O. M. Tsiroulnikova; S. A. Krasovsky; A. A. Mitrokhin; M. M. Vodneva; P. V. Sarygin; D. G. Akhaladze; E. А. Spirina (Вестник трансплантологии и искусственных органов, 2016)
Cystic fibrosis (CF) is the third most common indication for lung transplantation. The recipients with CF have shown the best early and late survival rates after surgery. The special group of CF patients consists of those, whose airways were infected with Burkholderia cepacia (B. cepacia), since the recurrence of B. cepacia infection after transplantation are coupled with extremely high risk of death. Up to the present, the question whether the patients in such conditions should be included onto the lung transplant waiting list is still unanswered. We describe a case of lung transplantation in the patient with late postoperative complication in the form of severe pyoseptic infl ammatory process caused by the recurrence of B. cepacia infection. The success of the treatment of this patient was achieved thanks to combined multidisciplinary approach. This therapeutic approach could be considered as a standard treatment protocol in case of its validation by further clinical experience.